Distributed and multi‐layer hierarchical controller placement in software‐defined satellite‐terrestrial network - Xu, Shuang; Wang, Hao; Fang, Yang; Zhao, Zhengpeng; Wang, Xingwei; Huang, Min (Transactions on emerging telecommunications technologies, 2024)
Aiming at the controller placement in software‐defined satellite‐terrestrial network, a distributed and multilayer hierarchical controller placement mechanism is proposed to improve the reliability and scalability. First, the metrics of network reliability, maintenance cost and usage cost are defined to establish the controller placement optimization model for the software‐defined satellite‐terrestrial network. Then, a distributed and hierarchical control structure composed of super controller, master controller, and slave controller is presented to enhance the scalability. Furthermore, according to the latitude variation of the LEO satellites, a time‐slot division method is proposed to staticize the network control topology. It reduces control link handover and enhances the stability of control links. In addition, a LEO satellite latitude based slave controller selection strategy and a shortest distance based inter layer control strategy are proposed to facilitate cost reduction and stability enhancement. Finally, extensive simulations demonstrate that the proposed control structure not only obtains high stability and scalability, but also efficiently saves the maintenance and usage cost. Besides, the impacts of service request distribution and satellite number on the control structure are analyzed. Aiming at the controller placement in software‐defined satellite‐terrestrial network, a distributed and multilayer hierarchical controller placement mechanism is proposed. It not only obtains high stability and scalability, but also efficiently saves the maintenance and use cost of control links and reduces adjacent channel interference.